Comparative Analysis of the Solid Phases of Bronchoalveolar Lavage and Oral Fluid in Children with Acute Necrotizing Pneumonia - V.N. Grona; Ye.A. Mozhayev; T.P. Tananakina; Yu.N. Modnaya (Zaslavsky O.Yu., 2014)
The growing number of acute lung abscesses, and pleural empyema, high invalidization and mortality determine the necessity for search of new methods of its diagnosis and treatment. The aim of this research was to study the morphological characteristics of in bronchoalveolar lavage and oral fluid facies in children with acute destructive pneumonias and to find out correlations between them. We examined 24 patients of department of purulent surgery in age from 1 to 14 years. Collection of mixed unstimulated oral fluid was carried out by spitting into special tubes, bronchoalveolar lavage was obtained by bronchoscopy. There has been revealed a correlation between morphological pattern of bronchoalveolar lavage and oral fluid in children depending on the pathological condition of the body.